Familial mediterranean fever complicated by chronic kidney disease stage 5 description of the clinical case - Maria Palchukovska; Lyudmila Liksunova (Bogomolets National Medical University, 2021)
this clinical case demonstrates renal amyloidosis - the most severe complication of familial Mediterranean fever (FMF). This clinical case gives an example of rapid evolution of renal failure in the lack of treatment. 62 years old man, Armenian, consults  a physician with such complaints as evening fever up to 38° for a month, frequent urination and dark urine. Biochemical blood test revealed an increase in the following indices: creatinine-489 μmol / l, urea 28.3 μmol / l, uric acid 619 μmol / l. GFR-6ml / min. No amyloid deposits were detected by biopsy of the buccal mucosa. The diagnosis of FMF, chronic kidney disease (CKD) stage 5. Initiation of treatment. Tenkhoff catheter installation. Treatment includes сontinuous ambulatory peritoneal dialysis (CAPD) in mode 4 exchanges with a glucose solution of 1.36% 2.0 liters. The dynamics of treatment is positive in  presence of constant replacement therapy. A feature of this clinical case is the insidious development of secondary (AA) amyloidosis in uncontrolled patient, which leads to the development of end-stage chronic kidney disease (CKD). This case demonstrates the need of constant examination and treatment of the patients with end-stage CKD by renal replacement therapy, which significantly reduces the quality of patient`s life.